MODEL KOMUNIKASI DALAM FILM ADIT SOPO JARWO EPISODE: BERSAHABAT AGAR KITA HEBAT - Meilita Teza Warman Warman; Oktri Permata Lani (JIKE: Jurnal Ilmu Komunikasi Efek, 2025)
The aim of this research is to identify various forms of communication that occur in the film "Adit Sopo Jarwo" episode "Be Friendly So We Are Great". Children's cartoons often convey moral messages and social skills through various modes of communication, both verbal and non-verbal. The importance of communication in the context of children's personal and social development. Through various animated characters and interesting stories. Cartoon films teach various aspects of communication, including expression, how to speak or interact well, active listening, and various ideas. This research uses a qualitative method with a semiotic approach modeled by Charles Sanders Peirce to analyze the use of signs or symbols in the film. This research is included in non-participatory research. Primary data was obtained from direct observation of the episode, while secondary data consisted of references from literature and related information sources. The analysis results show that this film depicts various forms of communication, including intrapersonal, interpersonal, verbal and non-verbal communication. For example, verbal communication when interacting uses words face to face, while non-verbal communication means nodding which means yes. Verbal and non-verbal communication is used effectively to convey emotions, ideas and moral messages about the importance of supporting friends and overcoming differences. Highlighting the importance of effective communication in the context of children's personal and social development, and how this film can play a role in educating viewers about the values ​​of friendship and solidarity.